The fetters of inheritance? Equal partition and regional economic development - Thilo R. Huning; Fabian Wahl (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2019)
How can agricultural inheritance traditions affect structural change and economic development in rural areas? The most prominent historical traditions are primogeniture, where the oldest son inherits the whole farm, and equal partition, where land is split and each heir inherits an equal share. In this paper, we provide a theoretical model that links these inheritance traditions to the local allocation of labor and capital and to municipal development. First, we show that among contemporary municipalities in West Germany, equal partition is significantly related to measures of economic development. Second, we conduct OLS and fuzzy spatial RDD estimates for Baden-Württemberg in the 1950s and today. We find that inheritance rules caused, in line with our theoretical predictions, higher incomes, population densities, and industrialization levels in areas with equal partition. Results suggest that more than a third of the overall inter-regional difference in average per capita income in present-day Baden Württemberg, or 597 Euro, can be explained by equal partition.
urn:nbn:de:bsz:100-opus-16711
Keywords: D02; D82; H11; H21; N93; 330; inheritance rules; sectoral change; regional economic development; Baden-Württemberg; spatial inequalities